2011
DOI: 10.1002/anie.201102552
|View full text |Cite
|
Sign up to set email alerts
|

Dye‐Sensitized Solar Cells Based On Donor–Acceptor π‐Conjugated Fluorescent Dyes with a Pyridine Ring as an Electron‐Withdrawing Anchoring Group

Abstract: Firmly attached: The short‐circuit photocurrent density and conversion yields of solar cells based on pyridine‐containing donor–acceptor π‐conjugated (D‐π‐A) dyes (see scheme) are greater than those for conventional D‐π‐A dye sensitizers that bear a carboxy group as the electron‐withdrawing anchoring group. The dyes are attached to the surface by coordinate bonding with the Lewis acid sites of TiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(140 citation statements)
references
References 27 publications
5
131
0
1
Order By: Relevance
“…When the dyes 3a-c were adsorbed on the TiO 2 surface, the stretching hands observed at 1517-1537 and 1569-1573 cm −1 have disappeared and a new strong band appeared at 1599-1600 cm −1 , which can be assigned to pyrimidinyl groups coordinated to the Lewis acid sites on the TiO 2 surface. These consequences are in good agreement with a similar behavior of the pyridinyl anchoring group [44][45][46][47][48][49][50] and with our previous results for the pyrimidinyl anchoring group [13].…”
Section: Photophysical and Electrochemical Propertiessupporting
confidence: 91%
“…When the dyes 3a-c were adsorbed on the TiO 2 surface, the stretching hands observed at 1517-1537 and 1569-1573 cm −1 have disappeared and a new strong band appeared at 1599-1600 cm −1 , which can be assigned to pyrimidinyl groups coordinated to the Lewis acid sites on the TiO 2 surface. These consequences are in good agreement with a similar behavior of the pyridinyl anchoring group [44][45][46][47][48][49][50] and with our previous results for the pyrimidinyl anchoring group [13].…”
Section: Photophysical and Electrochemical Propertiessupporting
confidence: 91%
“…The main objective of the present study was to determine whether photofunctional dyads such as 4 were efficient when attached to TiO 2 for electron photoinjection into the semiconductor. The most common method for attachment of light absorbers to TiO 2 nanoparticles is through various anchoring groups such as carboxylate, phosphonate, sulfonate, salicylate, acetylacetonate, catecholate, and hydroxamate (59)(60)(61)(62)(63)(64). In the present study, with phosphonate esters and carboxylate esters as diimine substituents on PtN 2 S 2 chromphores and dyads, attempts to hydrolyze the esters prior to TiO 2 attachment proved problematic because of poor stability of the PtN 2 S 2 moiety under the hydrolysis conditions.…”
Section: Resultsmentioning
confidence: 99%
“…2), which would be impossible in the case of isomer DF13A. This observation is not surprising, considering that even the simple pyridine ring has been reported to serve as anchoring group [14]. Based on these observations, device stability tests were also conducted on larger area, transparent cells, which indeed showed that devices built using compounds DF13B and DF13C retained their efficiency after 930 h of continuous simulated solar irradiation at 50 °C [27].…”
Section: Stability Tests Of the Dyesmentioning
confidence: 78%
“…2, right), which have interested various research groups. For instance, several dyes with a simple pyridine acceptor group have been prepared and showed to maintain a good charge injection efficiency in comparison with the corresponding carboxylic acids, although photovoltaic efficiencies often turned out to be only moderate at best [14][15][16][17][18][19][20]. Furthermore, a single example of a 2-carboxy-pyridine anchoring group was described, together with other heterocyclic, carboxylate-anchored, nitrogen-containing acceptors [21].…”
Section: Introductionmentioning
confidence: 99%